Analysis of immunizations against Human Virus Papilloma (HPV) in the state of Piauí (Research, Society and Development, 2020)
Human Papilloma Virus (HPV) is a virus with DNA capable of causing lesions on the skin and mucous membranes, which can cause warts or precursor lesions of cancer that can be classified as low and high oncogenic risk. The present study aimed to quantify and analyze the immunizations against HPV carried out in the state of Piauí. It was a documentary, retrospective, descriptive research with a quantitative approach. Data were collected from the Information System of the National Immunization Program (SI-PNI) through the doses applied, extracting the year, sex, age group and the number of doses of immunizations. Between 2014-2019, 482,763 doses of the quadrivalent vaccine were administered. Analyzing immunizations by year of administration, the following percentage distribution was obtained: 2014 (27%), 2015 (18%), 2016 (7%), 2017 (20%), 2018 (15%) and 2019 (13%). The vaccine administration in females (75%) was considerably higher than in males (25%). Individuals aged 11 years (24%) and 14 years (7%) are those who received the most and least, respectively, the vaccine doses. Regarding the doses required for prevention, there was a decrease in the percentage of doses applied, being distributed in the following frequency: 1st dose (58%), 2nd dose (41%) and 3rd dose (1%). The research made it possible to know the profile of immunizations against HPV in the state of Piauí. It is necessary to implement educational actions on HPV with the respective active search of individuals with incomplete schemes to achieve the goal of vaccination coverage.